Geothermal energy challenge : Guardbridge geothermal technology demonstrator project /: Guardbridge geothermal technology demonstrator project. (2016) - Rambøll (Firm); Town Rock Energy; University of St. Andrews; Resource Efficient Solutions LLP; British Geological Survey
No abstract available